Viperin and Its Effect on SVCV Replication in Common Carp, Cyprinus carpio - Yan Meng; Xi Hu; Nan Jiang; Yuding Fan; Yiqun Li; Mingyang Xue; Chen Xu; Wenzhi Liu; Yong Zhou (Animals)
Viperin is an interferon-stimulated gene (ISG) that plays an important role in the congenital antiviral immunity of vertebrates. In this study, the common carp viperin (cc-viperin) gene is characterized, and we determine whether it has the ability to inhibit spring viremia of carp virus (SVCV) replication in EPC cells. The results showed that the full-length cDNA of the cc-viperin gene was 1044 bp and it encoded 348 amino acids. The cc-viperin sequence contained a leucine zipper in the N-terminal, a CxxxCxxC motif in the SAM domain, and a conservative C-terminus. The cc-viperin gene’s nucleotide and amino acid sequence alignment revealed that cc-viperin displayed relatively high sequence identity compared with other species. Phylogenetic analysis displayed the close relation of cc-viperin with Carassius auratus and Mylopharyngodon piceus. Subcellular localization analysis indicated that the cc-viperin protein was located in the cytoplasm. The gene expression results showed that cc-viperin was expressed in all of the tissues tested. Its expression level significantly increased in EPC cells after 24 h to 72 h compared to the control during SVCV infection. Moreover, cc-viperin significantly inhibited SVCV replication when it was overexpressed, whereas it increased SVCV replication when it had reduced expression in EPC cells, respectively. To summarize, the results obtained in this work show that cc-viperin shares similar sequence characteristics with other vertebrates, and it could inhibit SVCV replication in EPC cells, displaying an antiviral effect in common carp.